2012
DOI: 10.1111/j.1744-7402.2011.02702.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Step Sintering of Pristine and Aluminum‐Doped Zinc Oxide Ceramics

Abstract: ZnO and Al-doped ZnO ceramics with high density and fine grain size were prepared using a two-step sintering method. ZnO ceramics with a grain size of 1.2 lm and a density greater than 99% were obtained. The kinetic window for a ZnO nanoparticle TSS process was determined in this study. Dense AZO ceramics with homogeneous Al distribution were obtained using a high sintering temperature (T st ) of 1323 K and a low sintering temperature (T nd ) of 1273 K. The activation energies for ZnO and AZO nanoparticle grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In order to determine the solid solubility limit, high temperature annealing of synthesized samples at 850 °C was followed. The formation of ZnAl 2 O 4 crystalline phase was selected as the criterion for solid solubility limit . Figure shows the XRD patterns of annealed samples with 1.5 and 2 at% Al 3+ at high temperature for 2 h. The formation of ZnAl 2 O 4 crystalline phase was not confirmed by XRD patterns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine the solid solubility limit, high temperature annealing of synthesized samples at 850 °C was followed. The formation of ZnAl 2 O 4 crystalline phase was selected as the criterion for solid solubility limit . Figure shows the XRD patterns of annealed samples with 1.5 and 2 at% Al 3+ at high temperature for 2 h. The formation of ZnAl 2 O 4 crystalline phase was not confirmed by XRD patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the Al 3+ ions solid solubility limit is the bottom line achieving better performance and long‐term stability of Al‐doped ZnO (AZO) nanostructures. Thus the challenge to improve the AZO performance will be concentrated on how to precisely define the solubility of Al 3+ and how to achieve its limit . The solubility of Al 3+ in ZnO which has been extensively investigated by researchers may widely vary in the range of 0.3–2.0 atomic ratio percents (at%) .…”
Section: Introductionmentioning
confidence: 99%
“…It can also be concluded that the kinetic window can be shifted up and down along the first-step temperature axis with the addition of dopants. So far, the kinetic windows have been proposed to Y 2 O 3 [15,19], Mg, Nb-doped Y 2 O 3 [15,19], ZnO [20], Ni-Cu-Zn ferrite [17], BaTiO 3 [17] and (1−x) BiScO 3−x PbTiO 3 (BSPT) [21].…”
Section: Sintering Mechanismmentioning
confidence: 99%
“…Electrical and optical properties of ZnO are mainly influenced by grain size. Grain growth of ZnO was successfully controlled using TSS [16,20,22,[74][75][76][77][78]. Zhang et al [20] and others [16] successfully sintered fully dense ZnO without grain growth at the final stage of sintering.…”
Section: Sintering Of Zinc Oxidementioning
confidence: 99%
“…In this step, the mobility of the grain boundary must be extremely slow, due to the locking of the triple junctions, but the diffusion by grain boundary must act, enabling densification. 6,16 TSS is used in many systems, such as PZT-PCN piezoelectric ceramics 17 and barium titanate, 18 hexagonal barium ferrite, 19 Al-doped zinc oxide, 20 hydroxyapatite, 21 Al 2 O 3 , 22 ZrO 2 , 23 and Al 2 O 3 /ZrO 2 system. 24,25 All these systems, sintered using TSS, in different materials, showed that microstructural control was possible.…”
Section: Introductionmentioning
confidence: 99%